Perilaku Jajan Pada Anak Sekolah Dasar Kelas IV, V, VI di SDN Sriamur 05 Kab Bekasi - Rahayu, Amefa Krismon Tika; Harini, Rika; Ponirah, Ponirah; Sunirah, Sunirah; Yeni, Roza Indra (Universitas Malahayati, 2023)
ABSTRACTChildren's health is an important part of human quality of life and cannot be separated from the food consumed by children every day. The current child health problem is the large number of school-age children who like to eat snacks in the school environment. The percentage of school snacks is 4.3% which contains hazardous ingredients. Factors that influence the selection of snacks in school-age children are knowledge, attitudes and behavior. Objective To get an overview of snacking behavior towards elementary school children in grades IV, V, VI. Methodology Using a Quantitative Descriptive Design with Univariate Analysis The sample used was random sampling of 176 respondents consisting of 3 classes, class IV, V, VI. The results of this study showed that the respondents were in their early teens (59.1%), female (59.7%), had good snacking behavior (67.6%). Conclusion The researchers concluded that the majority of respondents had good snacking behavior.Keywords: Elementary School Children, Snacking Behavior ABSTRAK Kesehatan anak merupakan bagian penting terhadap kualitas hidup manusia dan tidak lepas kaitannya dengan makanan yang dikonsumsi oleh anak setiap hari. Permasalahan kesehatan anak yang dialami saat ini adalah banyaknya anak usia sekolah yang gemar jajan di lingkungan sekolah. Presentase pangan jajanan sekolah sebesar 4,3% yang mengandung bahan berbahaya. Faktor yang mempengaruhi pemilihan jajanan pada anak usia sekolah adalah pengetahuan, sikap, dan perilaku. Tujuan Untuk mendapatkan gambaran perilaku jajan terhadap anak SD kelas IV, V, VI. Metodologi Menggunakan desain Deskriptif Kuantitatif dengan Analisa Univariat Sampel yang digunakan adalah random sampling sebanyak 176 responden terdiri dari 3 kelas, kelas IV, V, VI. Hasil Penelitian ini menunjukan responden pada usia remaja awal (59,1%), berjenis kelamin perempuan (59,7%), perilaku jajan baik (67,6%). Kesimpulan Peneliti menyimpulkan bahwa mayoritas responden berperilaku jajan baik.Kata Kunci: Anak Sekolah Dasar, Perilaku Jajan